Cataloging SCN resistance loci in North American public soybean breeding programs - Mahmood, Anser; Bilyeu, Kristin D.; Škrabišová, Mária; Biová, Jana; De Meyer, Elizabeth J.; Meinhardt, Clinton G.; Usovsky, Mariola; Song, Qijian; Lorenz, Aaron J.; Mitchum, Melissa G.; Shannon, Grover; Scaboo, Andrew M. (Frontiers in Plant Science, 2023)
Soybean cyst nematode (SCN) is a destructive pathogen of soybean responsible for annual yield loss exceeding 1.5 billion in the United States. Here, we conducted a series of genome-wide association studies (GWAS) to understand the genetic landscape of SCN resistance in the University of Missouri soybean breeding programs (Missouri Panel), as well as nd germplasm and cultivars within the United States Department of Agriculture (USDA) Uniform Soybean Tests -Northern Region (NUST). For the Missouri panel, we evaluated the resistance of breeding lines to SCN populations HG 2.5.7 (Race 1), HG 1.2.5.7 (Race 2), HG 0 (Race 3), HG 2.5.7 (Race 5) and HG 1.3.6.7 (Race 14) and identified seven quantitative trait nucleotides (QTN) associated with SCN resistance on chromosomes 2, 8, 11, 14, 17, and 18. Additionally, breeding lines in the NUST panel were evaluated for resistance to SCN populations HG 2.5.7 (Race 1) and HG 0 (Race 3), and three SCN resistance associated QTN were found on chromosomes 7 and 18. Through these analyses, we were able to decipher the impact of 7 major genetic loci, including three novel loci, on resistance to virulent several SCN populations and we also identified candidate genes within each locus. Further, we identified favorable allelic 2 This is a provisional file, not the final typeset article combinations for resistance to individual SCN HG types and provide a list of available germplasm for integration of these unique alleles into soybean breeding programs. Overall, this study offers valuable insight into the landscape of SCN resistance loci in U.S. public soybean breeding programs and provides a framework to develop new and improved soybean cultivars with diverse plant genetic modes of SCN resistance.